Cash Waqf in Normative and Economic Linkages - Ismatul Maula (GoAcademica Research & Publishing, 2022)
Socio-economic problems in society demand something new in achieving a more prosperous standard of living. Cash waqf has a big role in solving the problems of contemporary society. However, normatively, cash waqf is still being debated among fiqh experts, especially the Syafiiyyah school of thought, which tends to see waqf as the spirit of the immortality of objects, not benefits. This is certainly a problem for people affiliated with this school. However, positive law provides fresh air for the validity of cash waqf through Law Number 41 of 2004 concerning Waqf and Government Regulation Number 42 of 2006 concerning Implementation of Law No. 41 of 2004 concerning Waqf. In addition, the economic value of cash waqf has required the implementation of this cash waqf in order to spur economic activities of the people with religious and socio-economic dimensions for the realization of people's welfare.